2017
DOI: 10.1080/09503153.2017.1342791
|View full text |Cite
|
Sign up to set email alerts
|

An Inquiry by Social Workers into Evening Routines in Community Living Settings for Adults with Learning Disabilities

Abstract: Significant progress has been made since the 1980s in supporting adults with learning disability to live independent lives in the community. In 2012, the Department of Health in England announced the latest policy initiative to further invest in community support for people with learning disabilities, Transforming Care. Building the right community supported living setting for people does not in isolation provide for a comprehensive strategy towards achieving a paradigm shift in how people with learning disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The scope of use of the term 'supported living' in some cases was quite broad and non-specific, and was referred to in opposition to institutionalised living. In some cases supported living referred to people living in settings after deinstitutionalisation, but otherwise remaining in relatively congregated settings, such as community-based group homes (James, Harvey et al 2018). Other papers described different models of community-based living.…”
Section: Definitions Of Islmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of use of the term 'supported living' in some cases was quite broad and non-specific, and was referred to in opposition to institutionalised living. In some cases supported living referred to people living in settings after deinstitutionalisation, but otherwise remaining in relatively congregated settings, such as community-based group homes (James, Harvey et al 2018). Other papers described different models of community-based living.…”
Section: Definitions Of Islmentioning
confidence: 99%
“…These experiences contributed to diminished outcomes for people living in a setting and context where choice and autonomy were not facilitated. James, Harvey et al (2018) found that people with intellectual disabilities living in larger supported accommodation models-which were less aligned with a truly independent model, although still included in that paper-were experiencing regimented routines that were focussed on mealtimes and bedtimes, for the convenience of staff. This substantially limited their autonomy, choice and control.…”
Section: Contributing Factors To Negative Isl Outcomesmentioning
confidence: 99%